OPTIMALISASI HARMONI ISLAM MULTIKULTURAL BAGI MAHASISWA FAKULTAS TARBIYAH IAI HASANUDDIN PARE, KEDIRI - Zuli Dwi Rahmawati (LPPM Universitas Islam Darul 'Ulum Lamongan, 2025)
This service program was carried out as an effort to build an understanding of multiculturalism based on several online news reports about the rampant cases of bullying in the educational environment in Kediri district. The IAI Hasanuddin campus, which is located close to Kampung Anh Pare, faces unique social dynamics, a language education center that attracts students from various regions in Indonesia and even abroad, with very diverse religious, cultural, and ethnic backgrounds, although it provides great opportunities to learn from each other and exchange experiences, also gives a challenge in maintaining social harmony. This activity targets Tarbiyah students who are prepared as prospective educators and play an important role in shaping the character of the next generations so that they have a more comprehensive understanding of the importance of instilling multicultural values in the teaching and learning process. The Doctoral Teaching Group (KDM) of UNISMA Malang carried out this service using the Participatory Action Research (PAR) method. The results of the service show success that can be seen from the enthusiasm and positive response when discussing as an indication of improving the quality of human resources as the main capital for changes in social dynamics, so that this service can provide solutions to the needs of students of the Faculty of Tarbiyah IAI Hasanuddin Pare in supporting the government program of Strengthening Character Education (PPK) as an effort to realize the 2045 golden generation that is intelligent, character, competitiveness, and the spirit of Pancasila, the 1945 Constitution, the Republic of Indonesia, and Bhinneka Tunggal Ika.